Adoption mechanism of energy performance contracting (EPC) model in coal mine residual-heat utilization: An evolutionary game based analysis - Qiuhong Lai; Yan Dong (Cleaner Engineering and Technology)
This paper discusses how to promote the development of energy performance contracting (EPC) model of coal mine residual-heat utilization from the micro level. Firstly, this paper analyzes the response and behavior expression of various stakeholders in the EPC model of coal mine residual-heat utilization from a behavioral perspective. Secondly, the paper analyzes the stability and interaction mechanism of the strategic choice among governments, energy service companies (ESCOs) and coal mine enterprises by using the evolution game, and discusses key parameters that affect the strategic choice of stakeholders. Finally, the sensitivity analysis of selected parameters is discussed in details. Results show that: (1) the initial intentions of stakeholders influence the trajectory of development, but not the final trend. (2) In order to promote the EPC model to be actively adopted in coal mine residual-heat utilization industry, it is necessary to strengthen government incentives and supervision in the early stage. (3) Increasing the cost of coal mine enterprises' efforts to choose self-energy conservation, increasing the revenue sharing ratio of ESCOS and reducing the cost of ESCO's efforts, which is of great significance for promoting the market-oriented development of the EPC model in the coal mine residual heat utilization industry, as well as for China's energy conservation, emission reduction, and ''dual carbon'' goals.